Silent Struggles: Relative Energy Deficiency in Sport (REDs) in Female Athletes - Veronica Szygalowicz (The Journal for Undergraduate Ethnography)
Relative Energy Deficiency in Sport (REDs) is a condition caused by prolonged periods of reduced energy intake relative to expenditure, specifically in sport. Although estimates of prevalence vary, most of the athletic population likely suffers from REDs. This interview-based project examined the state of REDs knowledge, awareness, and practices in female athletes and those working with them. Female athletes were the primary focus given their relative absence from existing research. Results from this project suggest that most cases of REDs are caused by unintentional nutrient restriction with parents, society, and social media spreading poor nutrition information and behaviors that athletes eventually adopt. Identifying and treating REDs is complicated by the need for cooperation from athletes, who may be unaware of their inadequate fueling practices or are intentionally hiding their restrictive behaviors. Obtaining an official diagnosis is often a complex and lengthy process, with many healthcare professionals working together to exclude other potential medical conditions. Overall, this study suggests that at-large REDs education is necessary for athletes and those working with them. Additionally, implementing REDs screening practices, employing dietitians, and making support and similar resources available at sports institutions may decrease the prevalence of REDs and expedite the identification and treatment process.